Implementasi Genogram dalam Meningkatkan Perencanaan dan Keputusan Karier - Agus Afriliyanto; Maria Margaretha Sri Hastuti (Universitas Muria Kudus, 2021)
The objectives of this study were: to describe the improvement of planning and career planning for class XI TKJ 1 SMK Mambaul Falah Kudus after receiving guidance through a media genogram. The research method used in this research is Classroom Action Research. This research was conducted in four stages; Planning; Implementation; Observation; and Reflection. This research was conducted at SMK Mambaul Falah Kudus, the research subjects were students of class XI TKJ 1. Data collection techniques used observation and interview techniques. The data analysis technique used quantitative descriptive. The results showed that planning and career decisions in class XI TKJ SMK Mambaul Falah Kudus had increased. Pre cycle score obtained 37% category (Very Poor), cycle I increased with a score of 55% category (Less), cycle II increased to 74% category (Good). The conclusion in this research is that planning and career decisions in class XI TKJ 1 SMK Mambaul Falah Kudus have increased.